Particle size optimization enabled high initial coulombic efficiency and cycling stability of micro-sized porous Si anode via AlSi alloy powder etching. (10th October 2019) - Cao, Weiyi; Han, Kai; Chen, Mengxun; Ye, Hongqi; Sang, Shangbin
Abstract: The practical application of Si anode is still severely hindered owing to its unsatisfactory electrochemical performance, especially including poor initial Coulombic efficiency and long-term cycling stability. In this work, AlSi alloy powder was applied as precusor to prepare micro-sized porous Si. In order to better understand the effect of particle size on both morphology and electrochemical performance, the particle size of AlSi alloy powder was optimized. The results show that the average diameter of micro-sized porous Si with different particle sizes are about 5, 10, 15 μm, respectively. Besides, the initial Coulombic efficiency of micro-sized Si exhibits an increasing trend with the increase of particle size of AlSi alloy powder. The micro-sized porous Si electrode etched from AlSi alloy powder in diameter of 30 μm exhibits an initial Coulombic efficiency of 83.5% and capacity retention of 81.25% after 200 cycles at current density of 1 A g −1 . The results could potentially provide a helpful guide for the scalable fabrication of micro-sized porous Si anode with high initial Coulombic efficiency and long-term cyclibility.